2022
DOI: 10.3390/molecules27031049
|View full text |Cite
|
Sign up to set email alerts
|

Coffee-Derived Phenolic Compounds Activate Nrf2 Antioxidant Pathway in I/R Injury In Vitro Model: A Nutritional Approach Preventing Age Related-Damages

Abstract: Age-related injuries are often connected to alterations in redox homeostasis. The imbalance between free radical oxygen species and endogenous antioxidants defenses could be associated with a growing risk of transient ischemic attack and stroke. In this context, a daily supply of dietary antioxidants could counteract oxidative stress occurring during ischemia/reperfusion injury (I/R), preventing brain damage. Here we investigated the potential antioxidant properties of coffee-derived circulating metabolites an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…The ROS-scavenging activities of phenolics are structurally attributed to the presence of a benzene ring-bound hydroxyl that can react with ROS, including hydroxyl, superoxide, and peroxyl radicals [ 16 ]. Phenolics also exhibit anti-inflammatory activities by regulation of signaling pathways, including NF-κB and MAPKs [ 17 , 18 ]. NF-κB, a transcription factor, is a transducer of extracellular stress stimuli to intracellular responses, which is associated with the production of various pro-inflammatory mediators, including inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), and cytokines [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ROS-scavenging activities of phenolics are structurally attributed to the presence of a benzene ring-bound hydroxyl that can react with ROS, including hydroxyl, superoxide, and peroxyl radicals [ 16 ]. Phenolics also exhibit anti-inflammatory activities by regulation of signaling pathways, including NF-κB and MAPKs [ 17 , 18 ]. NF-κB, a transcription factor, is a transducer of extracellular stress stimuli to intracellular responses, which is associated with the production of various pro-inflammatory mediators, including inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), and cytokines [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The evidence was further confirmed by Lemos and team [ 23 ], where CGA was found superior to perform antioxidant profiles and recorded an IR50 below 7.0 μg/mL. Recently, in an effort to reveal the antioxidant effects of CGA-derived circulating metabolites, an activation of the Nrf2/ARE pathway was demonstrated among coffee drinkers [ 24 ]. Consumption of coffee phytoextracts incremented nuclear localization and HO-1 expression.…”
Section: Coffee As Potent Antioxidantmentioning
confidence: 72%
“…Relieve cerebral ischemic damage by inhibiting ferroptosis and other methods [36]. An experiment on oxygen and glucose deprivation and recovery to simulate reperfusion showed that coffee byproducts reduce the accumulation of reactive oxygen species [37]. Eduardo M Ribeiro, et al found that coffee drinking was not associated with an increased risk of all-cause mortality and cardiovascular events in patients with previous myocardial infarction [38].…”
Section: Discussionmentioning
confidence: 99%